Different and Unpredictable Clinical Outcome of Ruptured Pulmonary Hydatid Cysts - Sheikhy, Kambiz (Tanaffos, 2015)
Most authors believe that the best treatment for pulmonary hydatid disease is surgical evacuation. Although albendazole has been used prophylactically before surgery, there are many reports about increased incidence of the rupture of cyst after albendazole therapy, which can cause some complications. In this case report we present a patient with bilateral pulmonary hydatid cyst that was ruptured after using albendazole and different strategies were used for management of each cyst.